Wind-induced dynamic performance of a super-large hyperbolic steel-truss cooling tower. (December 2020) - Ma, Ting-ting; Zhao, Lin; Chen, Ne-yu; Ge, Yao-jun; Zhang, Dong
Abstract: In order to study the wind-induced performance of super-large steel structure cooling towers, a super-large hyperbolic 216.3m-high cooling tower comprising a double-layer steel-truss structure with steel-sheet cladding was taken as a case study. The dynamic characteristics of this cooling tower were analyzed and compared with those of a similar-scale reinforced concrete cooling tower. Then, fluctuating wind loads measured in wind tunnel tests were applied directly to a structural finite-element model based on proper orthogonal decomposition and reconstruction of the wind pressures. The displacement response of the cooling tower was subsequently obtained by full transient dynamic analysis, and then the distribution characteristics of mean response, the mode participation contribution of the fluctuating displacement responses, the wind-induced vibration factors and the influence of structural damping ratio were investigated and compared with those of a concrete cooling tower. The comparison results mainly show that the steel-structure cooling tower has higher natural vibration frequencies, a lower-order number of lateral overturning mode (indicating a higher risk of overturning collapse), simpler resonant modes, smaller variance ratio of resonant component and weaker sensitivity of dynamic response to structural damping. The study results could assist in wind resistance design of similar super-large steel-structure cooling towers. Highlights: Wind-induced performance of a hyperbolic steel cooling tower was investigated. Dynamic properties of steel and RC cooling towers were compared. Characteristics of wind-induced response and the mode participation were analyzed. Wind-induced vibration factors of steel and RC cooling towers were compared. Influence of damping ratio on wind-induced vibration factors was investigated.